Cytotoxicity of citral against melanoma cells: The involvement of oxidative stress generation and cell growth protein reduction - Larissa Juliani Sanches; Poliana Camila Marinello; Carolina Panis; Tatiane Renata Fagundes; José Andrés Morgado-Díaz; Julio Cesar Madureira de-Freitas-Junior; Rubens Cecchini; Alessandra Lourenço Cecchini; Rodrigo Cabral Luiz (Tumor Biology)
Citral is a natural compound that has shown cytotoxic and antiproliferative effects on breast and hematopoietic cancer cells; however, there are few studies on melanoma cells. Oxidative stress is known to be involved in all stages of melanoma development and is able to modulate intracellular pathways related to cellular proliferation and death. In this study, we hypothesize that citral exerts its cytotoxic effect on melanoma cells by the modulation of cellular oxidative status and/or intracellular signaling. To test this hypothesis, we investigated the antiproliferative and cytotoxic effects of citral on B16F10 murine melanoma cells evaluating its effects on cellular oxidative stress, DNA damage, cell death, and important signaling pathways, as these pathways, namely, extracellular signal-regulated kinases 1/2 (ERK1/2), AKT, and phosphatidylinositol-3 kinase, are involved in cell proliferation and differentiation. The p53 and nuclear factor kappa B were also investigated due to their ability to respond to intracellular stress. We observed that citral exerted antiproliferative and cytotoxic effects in B16F10; induced oxidative stress, DNA lesions, and p53 nuclear translocation; and reduced nitric oxide levels and nuclear factor kappa B, ERK1/2, and AKT. To investigate citral specificity, we used non-neoplastic human and murine cells, HaCaT (human skin keratinocytes) and NIH-3T3 cells (murine fibroblasts), and observed that although citral effects were not specific for cancer cells, non-neoplastic cells were more resistant to citral than B16F10. These findings highlight the potential clinical utility of citral in melanoma, with a mechanism of action involving the oxidative stress generation, nitric oxide depletion, and interference in signaling pathways related to cell proliferation.